ESTIMATE POPULATION OF LONG-TAILED MACAQUE MACACA FASCICULARIS (PRIMATES: CERCOPITHECIDAE) IN CALIK RIVER, SOUTH SUMATRA - Iqbal, Muhammad; Setiawan, Arum; Setiawan, Doni; Pormansyah; Saputra, Rio Firman; Indriati, Winda; Sulistyadi, Eko; Maharadatunkamsi; Yustian, Indra (Unmuh Babel Press, 2023)
Long-tailed Macaque Macaca fascicularis is recently considered Endangered primate based on the assumption of rapid decline due to the heavy demand in trading. To look at recent data of this Endangered primate, we conduct a mega transect survey on 5 June 2022 and 10-15 June 2022, to assess the populatons on M. fascicularis along 115 km of Calik River, South Sumatra Province, Indonesia. We use direct observation to census all individuals of M. fascicularis. Our survey found a total of 1.194 individuals of M. fascicularis were encountered in Calik River. Based on the survey coverage, it is presumed that the population of M. fascicularis in this area could reach 2.000 individuals. Due to the high population, it was confirmed that this primate has become a pest for the major crops of local people. In addition, no indication of hunting or observation of local people who keep M. fascicularis as a pet. Our survey suggests M. fascicularis is the most common species in riverine habitats.